Fasilitas Perbankan Digital sebagai Katalisator Pemberdayaan Ekonomi Masyarakat: Studi kasus Implementasi ATM/CRM oleh Bank BRI - Ida Ayu Nuh Kartini; Eva Dwi Fani; Aulia Afifah; Tansa Sugi Karenia (Jurnal Pelayanan Masyarakat, 2025)
This Community Service Program aims to enhance the understanding of parents, Madrasah Tsanawiyah students, and the community of Karangbong Village regarding the history of developmental psychology and major child development theories. The program was initiated due to the community’s limited knowledge of developmental concepts, which affects the quality of parenting practices. Using a descriptive qualitative approach through observation, interviews, educational sessions, and discussions, the program presented essential materials covering the history of developmental psychology, Piaget’s cognitive development theory, Erikson’s psychosocial stages, and Vygotsky’s sociocultural theory. The results indicate a significant improvement in participants’ comprehension of developmental stages and their ability to apply appropriate parenting strategies. The program also reinforced the awareness that child development is a responsibility and divine trust that must be nurtured optimally. Overall, this activity contributes to the development of informed, adaptive, and development-oriented parenting within the community.